SPECIFIC ASPECTS OF EARLY DETERMINATION OF STUDENTS’ SPORTS TALENT - Turg‘unov , Baxtiyor O‘ralovich (Innovative Development in Educational Activities, 2023)
The main reasons for the inability of primary school children to objectively assess the capabilities of their desires are the selection of gifted students and their targeted training.